Information Technology Infrastructure and Its Relationship with Talent Management: Applied on the Egyptian Meteorological Authority - Sayed, Omnia Hamdi; Shokr, Laila Hosam El Din; Al-Agry, Dina Farouk (The Arab Journal of Administration, 2024)
The purpose of this research is to examine the relationship between Information Technology Infrastructure and talent management at the Egyptian Meteorological Authority. The study relied on a descriptive analytical approach. A questionnaire two-part was designed and distributed to the respondents. The first part measures IT Infrastructure, and the second part measures talent management, to collect primary data and verify its validity and reliability. The research was conducted on a sample of 384 respondents, with a response rate 92.2%. Several conclusions were reached, the most important of which are: the availability of IT infrastructure was medium, and the practice of talent management was low. In addition, the research showed a statistically significant impact of IT infrastructure (Data Base, knowledge workers) on talent management. The research provided recommendation to assist decision makers in general and at the Egyptian Meteorology Authority in particular on the effective usage of IT to manage talent and overcome the problem of skilled labor leakage.